The Religion of Victory, the Cult of a Superpower. The Myth of the Great Patriotic War in the Contemporary Foreign Policy of the Russian Federation - Maria Domańska (Review (Institute of National Remembrance))
The glorification of the Soviet victory over Nazism is the focal point of Russia’s politics of history and an element of the ideological offensive that aims to legitimise Russian great-power ambitions. The narrative centred on the victory has a strong religious, not to say, messianic dimension. It aims to whitewash the dark chapters of Soviet history and legitimise the wars Moscow waged after 1945. According to the contemporary neo-Soviet interpretations, these wars were always defensive and justified by external circumstances. At the same time, distinctly anti-Western rhetoric is becoming more and more perceptible in Russian propaganda. The repeated accusations of “eternal” attempts by the West to destroy Russia and destabilise the global order are intensifying. The official discourse is marked by the nostalgia for the lost empire and the “concert of powers” that was established at the Yalta conference; it also seeks to justify violence as a tool of foreign policy. Its overriding aim is to legitimise the authoritarian regime and Moscow’s contemporary strategic goals, such as the hegemony in the post-Soviet area and the reshaping of the European security architecture. The official narrative is promoted by the state institutions, the educational system, the Kremlin-controlled media outlets and a network of social organisations subsidised by the state. It is also safeguarded by the administrative and criminal law and the apparatus of repression.